Three essays on health and labour market participation - Berthung, Espen (UiT The Arctic University of Norway, 2023)
‘Good health for all’ and ‘employment for all’ are two widely agreed-upon goals in Norwegian politics. Nevertheless, considerable inequalities in health exist, and the economic sustainability of public pensions is pressured by a substantial increase in life expectancy. Improving our understanding of inequalities in health and the relationship between health detriments and labour market participation (LMP) can help policymakers identify where and how policy strategies should be implemented. Subsequently, this can improve individuals’ health and make society more economically sustainable in transitioning to longer working life. This thesis aims to improve our knowledge of inequalities in health and the relationship between health detriments and individuals’ LMP. More specifically, this thesis investigates the effects of parental health, childhood financial conditions, and own education on individuals’ adult health. Moreover, the thesis investigates the relative importance of these three sets of variables for individuals’ health. Furthermore, this thesis compares the impact of three different health detriments on individuals’ LMP. Proxies for health detriments are stroke, heart attack, and three cancer severity levels. In addition, it investigates if there exists heterogeneity in the impacts by education. Finally, this thesis investigates if individuals’ resilience moderates the effect of health shocks on individuals’ LMP. I find that parental health, childhood financial circumstances (CFC), and individuals’ education creates lasting inequalities in health. Furthermore, individuals’ education and CFC have similar magnitudes, i.e., the gaps between the top and bottom levels in the CFC variable and individuals’ education are approximately the same. In addition, I find that parental health and CFC are each as important for their health as own education. Moreover, I find that cancer with a poor survival prognosis leads to the greatest reduction in LMP, followed by stroke, cancer with an intermediate survival prognosis, ...